Budaya Organisasi dalam Lembaga Islam - Asep Iwan Setiawan (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2015)
Every organization has a culture that aims to make every member can have a handle in the pursuit of goals. Organizational climate will become less favorable, the relationship between the employee will only be limited to normal relations without guided by the spirit of togetherness that is bound by the same values. Therefore every individual of a very important part of the organization upholding cultural values developed from year to year, which is rooted in strong values that will give birth to the employees believed a strong commitment. If this is ignored it will produce less karayawan commitment, motivation and performance levels of employees who are not satisfactory, which in turn will damage the company itself.